Proprotein Convertase Subtilisin/Kexin Type 9 Promotes Gastric Cancer Metastasis and Suppresses Apoptosis by Facilitating MAPK Signaling Pathway Through HSP70 Up-Regulation - Xu, Beili; Li, Shuyu; Fang, Yong; Zou, Yanting; Song, Dongqiang; Zhang, Shuncai; Cai, Yu (Frontiers in Oncology, 2021)
Objective: To examine the effect of proprotein convertase subtilisin/Kexin type 9 (PCSK9) on gastric cancer (GC) progression and prognosis, and to explore the un-derlying mechanism. Methods: PCSK9 expression levels in human GC tissues were determined by quan-titative real-time PCR, western blotting and immunohistochemical assay. PCSK9 se-rum levels were detected by enzyme-linked immunosorbent assay. The relationships of PCSK9 and GC progression and survival were analyzed using Chi-square test, Kaplan-Meier analysis and Cox proportional hazards model. The effect of PCSK9 on cell invasion, migration and apoptosis were determined in human GC cell lines and mouse xenograft model separately using PCSK9 knockdown and overexpression strategies. The PCSK9 interacting molecules, screened by co-immunoprecipitation combined with LC-MS/MS, were identified by immunofluorescence localization and western blotting. Additionally, the mitogen-activated protein kinase (MAPK) path-way was assessed by western blotting. Results: PCSK9 mRNA and protein levels were significantly elevated in GC tissues compared with the paired normal tissues at our medical center (P<0.001). Notably, the up-regulation of PCSK9 expression in GC tissues was related with tumor pro-gression and poor survival. GC patients had higher serum levels of PCSK9 than the age-matched healthy controls (P<0.001); PCSK9 promoted invasive and migratory ability and inhibited apoptosis in GC cells with no apparent affection in cell prolifer-ation. The silencing of PCSK9 reversed these effects, suppressing tumor metastasis in vitro and in vivo. Furthermore, PCSK9 maintained these functions through up-regulating heat shock protein 70 (HSP70), ultimately facilitating the mito-gen-activated protein kinase (MAPK) pathway. Conclusion: Collectively, our data revealed that high PCSK9 expression levels in GC tissue were correlated with GC progression and poor prognosis, and that PCSK9 could promote GC metastasis and suppress apoptosis by facilitating MAPK signaling pathway through HSP70 up-regulation. PCSK9 may represent as a novel potential therapeutic target in GC.